A reduced switch stress common-ground boosting multilevel inverter for renewable energy applications - Mohammad Zaid; Mohammad Ali; Adil Sarwar; Muhammad Khalid; Atif Iqbal (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Renewable energy sources like solar photovoltaic (solar-PV), and the battery storage system require DC-AC converters (inverters) to deliver power to the grid or standalone loads. The operation requires obtaining a sinusoidal voltage waveform at the output, and multilevel inverters (MLIs) produce better-quality waveforms than conventional two-level inverters. Switched-capacitor MLIs (SCMLI)are one typr of inverters that utilize the DC-capacitors as sources and get charged through the DC source. Additionally, they have recently shown their efficacy through reduced components and generating boosted output voltage. However, most topologies lack common-ground structures and are liable to be subjected to high-frequency leakage currents when connected to the solar-PV through parasitic capacitance. On the other hand, the recent common-ground quadruple-boost SCMLI topologies exhibit high switch-blocking voltage (6 or 8 times Vdc). To address these issues, this paper proposes a new nine-level quadruple-boost common-ground inverter (9LQBCGI) suitable for microinverter applications, whose maximum switch stress is equal to the output voltage (4Vdc), and uses twelve switches, three self-balanced capacitors, and one diode. Further, a simple single resistance-relay-based soft-starting is performed, which results in a low starting inrush current. The proposed SCMLI is structurally and economically compared with recent nine-level, four-times boosting topologies. Reliability analysis has also been performed using Markov model. The operational verification is performed in simulation on MATLAB/Simulink and PLECS, and on a hardware prototype in the laboratory environment.